(untitled) (Annals of Medical Research, 2021)
Aim: The aim of this study was to compare the clinical results of two different surgical approaches for patients with recurrent lumbar disc herniation. Furthermore, we retrospectively analysed both groups and compared preoperative radiological features, which may be useful to select most appropriate surgical technique. Materials and Methods: 36 patients underwent mini-open microdiscectomy and 14 patients underwent microdiscectomy with fusion surgery for recurrent lumbar disc herniation in our institution between 2007-2017. Patient’s demographic characteristics and clinical results, as well as preoperative radiological features (such as disc height, disc degeneration, facet joint angle on sagittal and axial plane, existence of foraminal stenosis or previous facetectomy, facet joint degeneration, adjacent segment degeneration, sagittal instability, coronal instability) were retrospectively analyzed and compared between two groups. Results: There were no statistically significant differences between the groups in terms of postoperative visual analog scale and Oswestry Disability Index scores. The mean age, mean duration of hospital stay and operation time were significantly lower in microdiscectomy group (p=0.003, p0.001, p0.001, respectively). There was no recurrence during a mean follow-up of 54.3 months. Disc degeneration grade, degree of foraminal stenosis and facet joint degeneration, sagittal instability grade, facetectomy rate, adjacent segment degeneration and number of microdiscectomies are statistically higher in stabilization group than simple microdiscectomy group (p0.001, p0.001, p0.001, p0.001, p0.001, p=0.047, p=0.010, respectively). Furthermore, sagittal and axial facet joint angles are significantly higher in the microdiscectomy group than the fusion group (p0.001, p0.001, respectively).Conclusion: Preoperative radiological evaluation of patients with recurrent disc herniation can help physicians in order to select the most appropriate surgical approach and therefore minimize surgical risks.